Love Letters for Joy - See, Melissa (Scholastic Press, 2023)
Less than a year away from graduation, seventeen-year-old Joy is too busy overachieving to be worried about relationships. She's determined to be Caldwell Prep's first disabled valedictorian. And she only has one person to beat, her academic rival Nathaniel. But it's senior year and everyone seems to be obsessed with pairing up. One of her best friends may be developing feelings for her and the other uses Caldwell's anonymous love-letter writer to snag the girl of her dreams. Joy starts to wonder if she has missed out on a quintessential high school experience. She is asexual, but that's no reason she can't experience first love, right? She writes to Caldwell Cupid to help her sort out these new feelings and, over time, finds herself falling for the mysterious voice behind the letters. But falling in love might mean risking what she wants most, especially when the letter-writer turns out to be the last person she would ever expect. --